PROVERBS AND ANTI-PROVERBS AS A MEANS OF PROMOTING AND ADVERTISING PRODUCTS IN THE GREEK OPEN-AIR MARKETS: AN ETHNOGRAPHIC APPROACH - Kouzas, Georgios (Proverbium - Yearbook, 2019)
This study presents the functionality of proverbs in a modern Greek open-air market. The study is based on the ethnographic research of an open-air market in the centre of Athens, which, apart from capturing traditional and modern proverbs within the urban space of Athens, aims, on the one hand, at depicting the communicative function of proverbs, and, on the other hand, at highlighting their importance in the advertisement of products and the commercial promotion of the latter.